2018
DOI: 10.1016/j.jclepro.2018.05.183
|View full text |Cite
|
Sign up to set email alerts
|

A study on air quality and heavy metals content of urban food produced in a Mediterranean city (Barcelona)

Abstract: a b s t r a c tUrban agriculture is growing in cities and is rising to the roofs of buildings. The potential food contamination is a key issue to be resolved to guarantee the health of consumers, and it affects both urban agriculture promoters and consumers. Crop contamination from the soil can be overcome by adopting a soilless cultivation system that, with good management practices, can also avoid contamination from the fertirrigation system and pest treatments. It has recently increased the number of soille… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 34 publications
1
29
0
1
Order By: Relevance
“…The validity of the environmental degradation-income per capita relationship has been subjected to plentiful studies within the last two decades, which is in alignment with the different indexes considered, and also with different linear and nonlinear methodologies applied [38,[45][46][47][48][49][50][51][52]. The deterioration of the environmental problems caused by carbon emissions and especially GHG emissions, the identification of the impacts of climate change on global economy [53], and the concepts of eco-efficiency sustainability under the context of the global economy supported motives for these theoretically approached scientific fields.…”
Section: Ekc Methodological Issuesmentioning
confidence: 99%
“…The validity of the environmental degradation-income per capita relationship has been subjected to plentiful studies within the last two decades, which is in alignment with the different indexes considered, and also with different linear and nonlinear methodologies applied [38,[45][46][47][48][49][50][51][52]. The deterioration of the environmental problems caused by carbon emissions and especially GHG emissions, the identification of the impacts of climate change on global economy [53], and the concepts of eco-efficiency sustainability under the context of the global economy supported motives for these theoretically approached scientific fields.…”
Section: Ekc Methodological Issuesmentioning
confidence: 99%
“…Urban spaces where food production takes place can be framed within urban green infrastructures, namely, multifunctional ecological areas (e.g., backyard, rooftop gardens, public gardens, and open spaces) that provide ecosystem services and benefits for human well-being (i.e., regulating, provisioning, supporting, cultural) [6,7]. Apart from food supply and nutrition issues, opportunities and benefits include the positive potentials for climate regulation [8], greenhouse gas emissions [9], air quality [10], biodiversity [11], storm-water runoff [12], rainwater harvesting [13], cultural and health issues [14], while controversies are reported for water resources [15,16]. Furthermore, UA can represent an interesting way of saving money reducing the budget earmarked for the purchase of fresh food [17].…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, it is important to acknowledge that previous studies concluded that the origin of pollutants in the urban environment is largely human (Khan et al, 2008) and that food contamination can occur either by contact with contaminated soils or by air pollution (Khan et al, 2016;Voutsa et al, 1996) that can be generated by different sources, such as wheeled transport emissions (Manta et al, 2002), previous land uses and atmospheric deposits from industrial activities and incinerators (Chen et al, 2005;Vittori Antisari et al, 2013). RA has an advantage because no urban soil is used and heavy metal pollution risk in UA depends mostly on the previous uses of the soil (Ercilla-Montserrat et al, 2018;Pennisi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding food safety, the dissemination of results from research on the risks of UA might contribute to boosting acceptance (Specht and Sanyé-Mengual, 2016), as it was demonstrated that risk is low and mostly linked to the previous uses of soil (e.g., incinerators, industry) (Vittori Antisari et al, 2013). Thus, RA has an advantage because no urban soil is used, and the location (roofs) is further from sources of air contamination (Ercilla-Montserrat et al, 2018;Pennisi et al, 2016). Moreover, the RTG is also protected from the exterior environment due to material insulation.…”
Section: Discussionmentioning
confidence: 99%